EFL students’ speaking ability in descriptive text - Yunda Lestari (Program Studi Pendidikan Bahasa Inggris, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah Cirebon, 2021)
This study aimed to find out EFL students’ speaking ability in a descriptive text. This research was a descriptive survey. The participants were chosen by using cluster random sampling technique where there were twenty students at the eleventh-grade students of SMA Negeri 4 OKU. The data were collected through oral test in the form of online test and telephone survey. WhatsApp application was used as an online platform in data collection. The result of the study showed that the total of students’ score was 1142 and mean of the students’ score was 57,1. There were 1 student (5%) who gains score 80-100 in very good criteria, 2 students (10%) who gain score 66-79 in good criteria, 10 students (50%) who gain score 56-65 in enough criteria, 5 students (25%) who gain score 46-55 in low criteria, and 2 students (10%) got score 45 in fail criteria. Based on the data, there were only 13 students (65%) who passed the students’ speaking ability. In conclusion, the frequency of criteria of students’ speaking ability is in enough criteria. Key words: EFL; Speaking abilit; Descriptive text